STRATEGI PEMASARAN BANK SYARIAH DALAM MENINGKATKAN DAYA SAING DI ERA DIGITAL - dewi fitriana; Muhammad Iqbal fasa (Jurnal Intelek Dan Cendikiawan Nusantara, 2024)
This research discusses marketing strategies for Islamic banks in increasing competitiveness in the digital era. Islamic banking in Indonesia has experienced significant growth, but still faces various challenges such as low understanding, limited technology and infrastructure. By utilizing digital technology such as social media, mobile banking, and collaboration with fintech, Islamic banks have a great opportunity to expand the market and increase operational efficiency. Digital marketing has proven effective in reaching a wider audience at lower costs, as well as improving customer experience. However, Islamic banks also face challenges such as the quality of human resources and cyber security threats. This research uses a qualitative method with a literature study approach for the opportunities and challenges of sharia bank marketing strategies in the digital era. The results show that Islamic banks need to continue to innovate in the use of technology to remain competitive amidst the development of the digital economy. Innovation and strengthening digital security systems are the keys to success in facing these challenges.